Outcomes of covered stents versus bare-metal stents for subclavian artery occlusive disease - Wei, Libing; Gao, Xixiang; Tong, Zhu; Cui, Shijun; Guo, Lianrui; Gu, Yongquan (Frontiers in Cardiovascular Medicine, 2023)
Objective: To compare the clinical efficacy of covered stents and bare-metal stents in the endovascular treatment of subclavian artery occlusive disease.Methods: Between January 2014 and December 2020, 161 patients (112 males) underwent stenting of left subclavian arteries; CSs were implanted in 55 patients (34.2%) and BMSs in 106 (65.8%). Thirty-day outcomes, mid-term patency, and follow-up results were analyzed with Kaplan-Meier curves. Relevant clinical, anatomical, and procedural factors were evaluated for their association with patency in the two groups using Cox proportional hazards regression.Results: Mean follow-up was 45 ± 18 months. The primary patency was 93.8% (95 % CI, 81.9% -98.0%) in the covered stent group and 73.7% (95 % CI, 63.2%-81.6%; P = 0.010) in the bare-metal stent group. The primary patency in the total occlusion subcategory was significant in favor of CS (93.3%, 95 % CI, 61.26%-99.0%) compared with BMS (42.3%, 95 % CI, 22.9%-60.5%; P = 0.005). Cox proportional hazards regression indicated that the use of BMSs (hazard ratio (HR), 4.90; 95 % CI, 1.47-16.31; P = 0.010) and total occlusive lesions (HR, 7.03; 95 % CI, 3.02-16.34; P < 0.001) were negative predictors of patency, and the vessel diameter (HR, 3.17; 95 % CI, 1.04-9.71; P = 0.043)) was a positive predictor of patency.Compared with bare stents, covered stents have a higher midterm primary patency in the treatment of subclavian artery occlusive disease.